2013
DOI: 10.1186/1479-5876-11-174
|View full text |Cite
|
Sign up to set email alerts
|

Betaine supplement enhances skeletal muscle differentiation in murine myoblasts via IGF-1 signaling activation

Abstract: BackgroundBetaine (BET) is a component of many foods, including spinach and wheat. It is an essential osmolyte and a source of methyl groups. Recent studies have hypothesized that BET might play a role in athletic performance. However, BET effects on skeletal muscle differentiation and hypertrophy are still poorly understood.MethodsWe examined BET action on neo myotubes maturation and on differentiation process, using C2C12 murine myoblastic cells. We used RT2-PCR array, Western blot and immunofluorescence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 51 publications
(73 reference statements)
4
57
0
1
Order By: Relevance
“…The insulin‐like growth factor‐1 (IGF‐1) is a well‐known regulator for foetal development and postnatal growth (Hellström et al., ). The growth‐promoting effects of MD on foetus are thought to be mediated through IGF‐1 (Apicella et al., ; Lee, Kim, Park, & Kang, ; Senesi, Luzi, Montesano, Mazzocchi, & Terruzzi, ). In fact, the IGF‐1 gene promoters and coding regions contain multiple CG sites that are subjected to differential methylation (Fu, Yu, Callaway, Lane, & Mcknight, ; Zhao, Yang, Hu, Dong, & Zhao, ).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin‐like growth factor‐1 (IGF‐1) is a well‐known regulator for foetal development and postnatal growth (Hellström et al., ). The growth‐promoting effects of MD on foetus are thought to be mediated through IGF‐1 (Apicella et al., ; Lee, Kim, Park, & Kang, ; Senesi, Luzi, Montesano, Mazzocchi, & Terruzzi, ). In fact, the IGF‐1 gene promoters and coding regions contain multiple CG sites that are subjected to differential methylation (Fu, Yu, Callaway, Lane, & Mcknight, ; Zhao, Yang, Hu, Dong, & Zhao, ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that BET enhances neo myotubes formation and differentiation while promoting IGF-I gene and protein expressions in C2C12 murine myoblasts [6], a model of skeletal muscle development [7]. IGF-I has long been known to play a role not only in muscle hypertrophy but even in bone strength [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they develop a system of defenses that represent an excellent example of redox balance maintenance [24]. Interestingly, we showed that protein and catalytic breakdown can be reversed by arginine but not by glycerol, benzylhydantoin and betaine which all might act as a chaperone as recently proposed for unrelated metabolic disorders [25][27]. Also, another mechanism may be proposed concerning the effective role of L-arginine on aldolase A activity, namely its antioxidant function via increased NO formation and reduced release of superoxide.…”
Section: Discussionmentioning
confidence: 56%
“…Three other chaperons (sigma) were also tested, glycerol (100 mM) [25] for 10 days, betaine (10 and 50 mM) [26], [27] and benzylhydantoin (130 µM) for 3 days. Uniformly stable isotope labeled (U- 13 C 5 ) glutamine or (U- 13 C 6 ) arginine (Eurisotop, Saint-Aubin, France) were provided to myoblasts (1 mM) in the presence of glucose (2.5 mM) and incubated without serum for 6 hours.…”
Section: Methodsmentioning
confidence: 99%